Análise, caracterização e adequação de um sistema de cobertura do tipo gridshell para o Campus da UNESP/Itapeva - Freitas, Ulysses Martins de [UNESP] (2016)
This present paper aimed in overseeing a Gridshell construction, which is a roofing construction system. It has differentiated geometries, usually wavy ones. Several characteristics were analyzed in the structure, like shell behavior, structural elements dimensions, constructive and connections details, number of system elements and characterization and protection of the obtained structure. The chosen wood for the confection has a C40 resistance class and, likewise all the Lyptus woods (which are hybrids from Eucaliptus grandis and urophylla), needs a protection system against biological demand and also against the weather actions. The structure may be used as a disclosure for wood structures in the region of Itapeva, as it is considered light, which certainly may save money in the foundation system, as well as it may be used to start other researches about the subject, which are still scarce in Brazil